Strategic Planning Based Management In Digital Transformation And Its Impact On Management Systems (Architecture Image Studies, 2025)
In the modern era, the rapid advancement of technology and the expansion of digitalization fundamentally transform organizational management and strategic planning processes. Especially in fields such as higher education institutions, industrial organizations, and public administrations, digital transformation has become a core component of strategic approaches aimed at increasing organizational efficiency and enhancing competitive advantage. This study examines the effects of digital transformation processes, based on strategic planning, on management systems. The research highlights the importance of digitalization in organizational decision-making, performance measurement, resource optimization, and agility. At the same time, it emphasizes the significance of effective management structures, transparency, and leadership for successful digital transformation. Within the scope of the study, strategic planning and digital transformation practices across various countries and sectors are comparatively analyzed, and the best management models are identified. The results show that digital transformation is not only a technological innovation but also an integral part of strategic management that is essential for sustainable development and achieving competitive superiority. In this context, the synergy between strategic planning and digital transformation accelerates organizational adaptation to changing environments and enhances the effectiveness of management systems. Overall, the study reveals ways to successfully implement digital transformation within the framework of strategic management and opens new perspectives for future research.